Small airways disease in mild and moderate chronic obstructive pulmonary disease: a cross-sectional study. Issue 8 (August 2018) - Koo, Hyun-Kyoung; Vasilescu, Dragoş M; Booth, Steven; Hsieh, Aileen; Katsamenis, Orestis L; Fishbane, Nick; Elliott, W Mark; Kirby, Miranda; Lackie, Peter; Sinclair, Ian; Warner, Jane A; Cooper, Joel D; et al.
Summary: Background: The concept that small conducting airways less than 2 mm in diameter become the major site of airflow obstruction in chronic obstructive pulmonary disease (COPD) is well established in the scientific literature, and the last generation of small conducting airways, terminal bronchioles, are known to be destroyed in patients with very severe COPD. We aimed to determine whether destruction of the terminal and transitional bronchioles (the first generation of respiratory airways) occurs before, or in parallel with, emphysematous tissue destruction. Methods: In this cross-sectional analysis, we applied a novel multiresolution CT imaging protocol to tissue samples obtained using a systematic uniform sampling method to obtain representative unbiased samples of the whole lung or lobe of smokers with normal lung function (controls) and patients with mild COPD (Global Initiative for Chronic Obstructive Lung Disease [GOLD] stage 1), moderate COPD (GOLD 2), or very severe COPD (GOLD 4). Patients with GOLD 1 or GOLD 2 COPD and smokers with normal lung function had undergone lobectomy and pneumonectomy, and patients with GOLD 4 COPD had undergone lung transplantation. Lung tissue samples were used for stereological assessment of the number and morphology of terminal and transitional bronchioles, airspace size (mean linear intercept), and alveolar surface area. Findings: Of the 34 patients included in this study, ten were controls (smokers with normal lung function), ten patients had GOLD 1 COPD, eight had GOLD 2 COPD, and six had GOLD 4 COPD with centrilobular emphysema. The 34 lung specimens provided 262 lung samples. Compared with control smokers, the number of terminal bronchioles decreased by 40% in patients with GOLD 1 COPD (p=0·014) and 43% in patients with GOLD 2 COPD (p=0·036), the number of transitional bronchioles decreased by 56% in patients with GOLD 1 COPD (p=0·0001) and 59% in patients with GOLD 2 COPD (p=0·0001), and alveolar surface area decreased by 33% in patients with GOLD 1 COPD (p=0·019) and 45% in patients with GOLD 2 COPD (p=0·0021). These pathological changes were found to correlate with lung function decline. We also showed significant loss of terminal and transitional bronchioles in lung samples from patients with GOLD 1 or GOLD 2 COPD that had a normal alveolar surface area. Remaining small airways were found to have thickened walls and narrowed lumens, which become more obstructed with increasing COPD GOLD stage. Interpretation: These data show that small airways disease is a pathological feature in mild and moderate COPD. Importantly, this study emphasises that early intervention for disease modification might be required by patients with mild or moderate COPD. Funding: Canadian Institutes of Health Research.